Equal but different! Improving care for older LGBT+ adults. (24th June 2022) - Bailey, Dan; Calasanti, Toni; Crowe, Andrew; di Lorito, Claudio; Hogan, Patrick; de Vries, Brian
Abstract: International human rights movements have improved the visibility and equality of lesbian, gay, bisexual and transgender+ (LGBT+) communities and their members. Health outcomes for LGBT+ people remain, however, worse than for their non-LGBT+ peers. Older LGBT+ people have experienced fewer positive changes, in part due to their lived experience of discrimination and their ongoing, unintentional invisibility in medical and social care. This article highlights the impacts of societal structure, health and social care on the lives of older LGBT+ people including physical and mental health, End of Life, Dementia, Housing and Care Settings, and a focus on the experiences of trans-people. We look at the existing improvements developed by LGBT+ communities (and their allies) and propose refreshing Person-Centred Care to improve inclusivity. Finally, we provide a framework for looking at the areas in which service challenges arise and suggest ways to address these to make health and social care services more ready to meet the needs of older LGBT+ people.